Dietary patterns of Pakistani adults and their associations with sociodemographic characteristics-a community based study - Rafique, Ibrar; Saqib, Muhammad Arif Nadeem; Murad, Nighat; Munir, Muhammad Kashif; Khan, Aftab; Irshad, Rabia; Rahat, Tayyaba; Naz, Saima (Journal of the Pakistan Medical Association, 2022)
Objective: To identify the dietary patterns and understand their association with sociodemographic characteristics among adults. Methods: The community-based cross-sectional study was conducted in Islamabad, Lahore, Karachi, Peshawar and Quetta cities of Pakistan from March to November 2018, after approval from the National Bioethics Committee, Islamabad, and comprised adults of either gender. Data was collected using the food frequency questionnaire, and dietary patterns were identified using factor analysis. Multivariate regression analysis was used to assess the association of socio-demographic determinants with dietary patterns. Data was analysed using SPSS 21. Parallel Analysis criterion (Eigen values) was determined along with Monte Carlo simulation. Results: Of the 448 subjects, 206(46%) were males and 242(54%) were females. The largest age group was 36-55 years 199(47.4%). Six dietary patterns were identified: “Vegetables”, “Fruits”, “Mixed Junk and Processed food”, “Dairy and Fast food”, “Discretionary” and “Fish”. Regression analysis showed that those aged 36-55 years had higher scores for vegetables, fruit and fish pattern (p<0.05). Females scored more for vegetables, fish and fruits, and a significantly low score for discretionary diet pattern (p<0.05). Participants with high education level and socioeconomic status had raised scores for discretionary diet items (p<0.05). Conclusion: Six distinct dietary patterns among Pakistani adults were identified, showing significant association with sociodemographic characteristics. Key Words: Healthy diet, Nutrition, Factor analysis, Diet pattern, Pakistan, Unhealthy diet.